Critica, totalità, mediazione. Note sulla lezione di Fortini - Corradi, Cristina (L’ospite ingrato, 2021)
Responding to some of the theses that emerged within the debate on “criticism and totality”, the article intends to broaden the ongoing discussion by proposing a different reading of the concepts of criticism, totality and dialectics. Starting from the particular emphasis given to this last term, useful moreover to understand the importance assumed by the dialectical procedure in the construction of a possible critical practice, the article focuses on the example offered by Franco Fortini’s lesson through the resumption of some fundamental points of his methodological approach, among which the concept of mediation stands out.